Epidemiological impact of a nationwide measles immunization campaign in Viet Nam: a critical review - Hitoshi Murakami; Nguyen Van Cuong; Hong Van Tuan; Katsuyuki Tsukamoto; Do Si Hien (The World Health Organization, 2008)
OBJECTIVE: To study the impact on measles case incidence of a nationwide measles immunization campaign in Viet Nam, while considering differences in disease surveillance before and after the campaign. METHODS: A nationwide mass immunization campaign was conducted in the north and south of Viet Nam in 2002 and 2003, respectively. During the campaign, a second vaccination dose was given to children aged 9 months to 9 years, and the reported coverage reached 99% in both zones. National measles case-based surveillance data collected during 2001-2006 were reviewed and analysed. Surveillance performance was assessed in terms of case investigation and specimen collection rates and reporting sensitivity for febrile rash cases. Fisher's exact test was used to test for differences in indicator values before and after the campaign at the national and regional levels; the Wilcoxon signed-rank test was used at the provincial level. FINDINGS: Despite significant improvements in disease surveillance, a dramatic reduction in observed measles incidence was noted nationwide after the immunization campaign, with a drop in the national incidence of confirmed measles cases per 100 000 population from 5.44 in 2001 to 0.14 after the campaign (i.e. 2003 in the north and 2004 in the south; P < 0.001). Rapid measles resurgence was observed in 2005 and 2006 only in the north-western mountainous region of the country. The north did not show a statistically significant age shift for new cases (median age: 9 years in 2001 versus 8 years in 2003; P = 0.113), whereas the south did (median age: 7 years versus 12 years; P < 0.001). CONCLUSION: A campaign approach for controlling measles in developing parts of Asia can prove effective. The swift re-emergence of disease in the north-western region was probably due to suboptimal coverage by the campaign and by the subsequent routine expanded programme on immunization in the north-western mountainous region.